2022
DOI: 10.26508/lsa.202201456
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autism-candidate CHD8 perturbs neural crest development and intestinal homeostatic balance

Abstract: Individuals with mutations inCHD8present with gastrointestinal complaints, yet the underlying mechanisms are understudied. Here, using a stable constitutivechd8mutant zebrafish model, we found that the loss ofchd8leads to a reduced number of vagal neural crest cells (NCCs), enteric neural and glial progenitors, emigrating from the neural tube, and that their early migration capability was altered. At later stages, although the intestinal colonization by NCCs was complete, we found the decreased numbers of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Previous studies on Chd8 -mutant mice and human neurons suggested multiple mechanisms that may underlie CHD8-related brain deficits ( Sugathan et al, 2014 ; Cotney et al, 2015 ; Wang et al, 2015 ; Breuss and Gleeson, 2016 ; Durak et al, 2016 ; Katayama et al, 2016 ; Gompers et al, 2017 ; Platt et al, 2017 ; Wang et al, 2017 ; Andreae and Basson, 2018 ; Jung et al, 2018 ; Suetterlin et al, 2018 ; Wade et al, 2018 ; Xu et al, 2018 ; Zhao et al, 2018 ; Hulbert et al, 2020 ; Jimenez et al, 2020 ; Sood et al, 2020 ; Cherepanov et al, 2021 ; Ding et al, 2021 ; Ellingford et al, 2021 ; Hurley et al, 2021 ; Kawamura et al, 2021 ; Kweon et al, 2021 ; Weissberg and Elliott, 2021 ; Chen et al, 2022 ; Coakley-Youngs et al, 2022 ; Dong et al, 2022 ; Haddad Derafshi et al, 2022 ; Jimenez et al, 2022 ; Kerschbamer et al, 2022 ; Lee et al, 2022 ; Paulsen et al, 2022 ; Thudium et al, 2022 ; Tu et al, 2022 ; Villa et al, 2022 ; Yu et al, 2022 ; Hayot et al, 2023 ). However, mechanisms underlying the male–female differences in CHD8-related ASD are poorly understood ( Jung et al, 2018 ; Cherepanov et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Chd8 -mutant mice and human neurons suggested multiple mechanisms that may underlie CHD8-related brain deficits ( Sugathan et al, 2014 ; Cotney et al, 2015 ; Wang et al, 2015 ; Breuss and Gleeson, 2016 ; Durak et al, 2016 ; Katayama et al, 2016 ; Gompers et al, 2017 ; Platt et al, 2017 ; Wang et al, 2017 ; Andreae and Basson, 2018 ; Jung et al, 2018 ; Suetterlin et al, 2018 ; Wade et al, 2018 ; Xu et al, 2018 ; Zhao et al, 2018 ; Hulbert et al, 2020 ; Jimenez et al, 2020 ; Sood et al, 2020 ; Cherepanov et al, 2021 ; Ding et al, 2021 ; Ellingford et al, 2021 ; Hurley et al, 2021 ; Kawamura et al, 2021 ; Kweon et al, 2021 ; Weissberg and Elliott, 2021 ; Chen et al, 2022 ; Coakley-Youngs et al, 2022 ; Dong et al, 2022 ; Haddad Derafshi et al, 2022 ; Jimenez et al, 2022 ; Kerschbamer et al, 2022 ; Lee et al, 2022 ; Paulsen et al, 2022 ; Thudium et al, 2022 ; Tu et al, 2022 ; Villa et al, 2022 ; Yu et al, 2022 ; Hayot et al, 2023 ). However, mechanisms underlying the male–female differences in CHD8-related ASD are poorly understood ( Jung et al, 2018 ; Cherepanov et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…74 75 Various animal models of monogenic forms of ASD have displayed disruptions to these muscular contractions. 43 76 77 78 79 In a clinical ASD population, any of these disruptions could alter GI transit, impairing food bolus and thus nutrient absorption, potentially resulting in increased hospitalization, malnutrition, and emergency department visits. 43 76 77 78 79 80…”
Section: Phelan-mcdermid Syndrome and Its Gi Comorbiditiesmentioning
confidence: 99%
“…74,75 Various animal models of monogenic forms of ASD have displayed disruptions to these muscular contractions. 43,[76][77][78][79] In a clinical ASD population, any of these disruptions could alter GI transit, impairing food bolus and thus nutrient absorption, potentially resulting in increased hospitalization, malnutrition, and emergency department visits. 43,[76][77][78][79][80] An NIH study by Witmer et al was one of few studies using both patient-reported outcome measures (PROMs), such as ROME IV criteria, and diagnostic testing in patients specifically with PMDS.…”
Section: Constipation and Gi Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The next session was "Regeneration & stem cells, aging, senescence." In this session, six speakers showed their results regarding the dynamics of gene expression in stem and progenitors cells from various tissues, such as during ectomesenchyme specification (Zalc et al, 2021) (Antoine Zalc, Cochin Institute), homeostasis of the intestine (Hayot, Massonot, Keime, Faure, & Golzio, 2023) (Mathieu Massonot, IGBMC Strasbourg), regeneration of the fin in zebrafish (Cudak, Lopez-Delgado, Keil, & Knopf, 2023) (Franziska Knopf, Center for Regenerative Therapies TU Dresden & Center for Healthy Aging, Medical Faculty TU Dresden) and aging process (Aiko Sada, Kumamoto University). Thereby illustrating beautifully how we need to expand our understanding of cell differentiation potential.…”
mentioning
confidence: 99%